The Influence of Behavioral Factors on the Use of the Polio Pin Program in Toddlers in the work Area of the West City Health Center - Muslihatul Iskamia; Herlina Jusuf; Yasir Mokodompis (Universitas Muhammadiyah Palu, 2025)
Polio is an infectious disease that causes permanent paralysis, especially in children of toddler age. The Indonesian government has implemented National Polio Immunization Week (PIN) to prevent the spread of this disease. However, the coverage of the program at the West City Health Center has not met the national target, which is only 75.1% of 95%. This study aims to analyze the influence of behavioral factors on the use of the Polio PIN program. Analytical survey research method with cross-sectional design. The sample amounted to 297 mothers who had toddlers aged 0–59 months, taken by purposive sampling technique. Data were collected using questionnaires and analyzed by binary logistic regression test. The results showed that knowledge, attitudes, access to health services, family support, and health worker support had a significant influence on the use of Polio PIN (p < 0.05). Meanwhile, income showed no significant influence (p = 0.119). Behavioral factors are an important factor in the success of immunization programs. Intensive education and counseling efforts need to be carried out to increase community participation.